Enhancing block cipher diffusion: A mathematical approach to key-dependent mix column transformations - Naserelden, Shiraz; Alias, Norma; Altigani, Abdelrahamn; Waheeb, Maher; Alazzam, Azmi; Elsadig, Muawia A.; Hilal, Hasan Abu (Edelweiss Applied Science and Technology, 2025)
In this paper, we propose a novel key-dependent MixColumn transformation to enhance the diffusion properties of block ciphers, specifically within the AES framework. The proposed method introduces dynamic variation into the MixColumn step by extracting a pseudo-random value from the round key, which is used to perform cyclic permutations on the MixColumn coefficients. This leads to the construction of a round-dependent transformation matrix, mathematically defined and proven to maintain invertibility over GF(2⁸). We provide a formal mathematical representation of the proposed model and analyze its diffusion characteristics, linear independence, and resistance to cryptanalytic attacks. Our approach eliminates static transformation patterns and introduces key-driven unpredictability, offering a promising direction for adaptive cryptographic primitives without increasing algorithmic complexity or requiring hardware modifications.